Coronary Sinus Pacing in Patients after Tricuspid Valve Surgery with Complete Atrioventricular Block - Rydlewska, Anna; Boczar, Krzysztof; Lelakowski, Jacek (Cardiology and Cardiovascular Medicine, 2019)
The tricuspid valve defects following implantation of heart stimulating devices receive more and more attention in literature. We present a case series of patients requiring permanent cardiac stimulation in whom the insertion of a lead through the tricuspid valve proved impossible.